Analisis Pentingnya Pendidikan Kewarganegaraan Mulitikultural Dalam Membentuk Kesadaran Pluralisme Social - Dewi Romantika Tinambunan; Jekson Saragih; Ture Ayu Situmeang; Ivana Theo Philia; Laras Sati Sintania (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Indonesia, as a multicultural country, faces challenges in managing religious, tribal, cultural, racial and ethnic diversity. Social conflict can arise as a result of these differences. Therefore, PKN has an important role in forming the character of citizens who respect diversity. This research aims to understand how multiculturalism can trigger social conflict and the role of PKN in forming awareness of social pluralism. The method used in this research is a qualitative approach literature study, which is carried out by conducting a study of theories related to the research topic. The results of the research show that the increase in the number of students with various ethnic, ethnic and religious backgrounds in higher education creates an environment that is full of diversity. It is hoped that PKN can help overcome this conflict by teaching the values ​​of multiculturalism and respecting diversity in everyd (estari, 2015)ay life. This study provides important insights for readers regarding the role of PKN in forming awareness of social pluralism amidst multiculturalism, as well as providing recommendations for strengthening social integration in Indonesia.